2024
DOI: 10.1093/gigascience/giae009
|View full text |Cite
|
Sign up to set email alerts
|

On the variability of dynamic functional connectivity assessment methods

Mohammad Torabi,
Georgios D Mitsis,
Jean-Baptiste Poline

Abstract: Background Dynamic functional connectivity (dFC) has become an important measure for understanding brain function and as a potential biomarker. However, various methodologies have been developed for assessing dFC, and it is unclear how the choice of method affects the results. In this work, we aimed to study the results variability of commonly used dFC methods. Methods We implemented 7 dFC assessment methods in Python and use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Previous investigations on multiscale entropy to assess signal complexity in AD showed that the directionality of the results depended on the time-scale for the parameter calculation, finding increased signal complexity in controls for short time-scales, and decreased for larger time-scales [60,61]. Consequently, comparing results from different studies is intricate, and multi-analysis studies are needed to better understand the relationship between different dFC metrics and improve comparability [62].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations on multiscale entropy to assess signal complexity in AD showed that the directionality of the results depended on the time-scale for the parameter calculation, finding increased signal complexity in controls for short time-scales, and decreased for larger time-scales [60,61]. Consequently, comparing results from different studies is intricate, and multi-analysis studies are needed to better understand the relationship between different dFC metrics and improve comparability [62].…”
Section: Discussionmentioning
confidence: 99%